Promoting Cancer Screening in Partnership With Health Ministries in 9 African American Churches in South Los Angeles: An Implementation Pilot Study - Maxwell, Annette E. (Prev Chronic Dis, 2019)
PURPOSE AND OBJECTIVES: We conducted a pilot study to assess the degree to which an intervention led by community health advisors (CHAs) to promote cancer screening was delivered as intended and to estimate the potential effect of the intervention on receipt of screening. In contrast to previous studies and to maximize its potential public health impact, the intervention targeted 4 screening tests and only participants who were not up to date with screening guidelines for at least 1 cancer. Because CHAs had to both determine baseline adherence and provide counseling on 4 screening tests, the protocol was complex. Complex protocols can reduce implementation fidelity. INTERVENTION APPROACH: In partnership with health ministries at 9 African American churches in South Los Angeles, we conducted a 1-group pretest–posttest pilot study to assess the feasibility of implementing the intervention. CHAs recruited and obtained consent from church members aged 50 to 75 years; assessed adherence to national screening guidelines for breast, cervical, colorectal, and prostate cancer; and provided evidence-based strategies (one-on-one counseling, print materials, reminder calls) to encourage screening for tests that were overdue. EVALUATION METHODS: We assessed implementation fidelity by reviewing baseline screening assessments and counseling scripts completed by CHAs. We estimated potential effect of the intervention on receipt of screening by using data from 3-month follow-up surveys, conducted by the research team, of participants who were nonadherent at baseline. RESULTS: From June 2016 to June 2018, 44 CHAs conducted baseline assessments of 775 participants, of whom 338 (44%) were nonadherent to national guidelines for 1 or more cancer screening tests. CHAs provided counseling to most nonadherent participants. At follow-up, about one-third of participants reported that they had discussed cancer screening with their provider and a smaller proportion reported receipt of a screening test; 13% of men and 25% of women reported receipt of colorectal cancer screening. IMPLICATIONS FOR PUBLIC HEALTH: This study demonstrates that with training and ongoing technical assistance, CHAs at African American health ministries can implement complex research protocols with good fidelity.